Muscle Tissue Damage and Recovery After EV71 Infection Correspond to Dynamic Macrophage Phenotypes - Lu, Mei-Yi; Lin, Ya-Lin; Kuo, Yali; Chuang, Chi-Fen; Wang, Jen-Ren; Liao, Fang (Frontiers in Immunology, 2021)
Enterovirus 71 (EV71) is a positive single-stranded RNA virus from the enterovirus genus of the Picornaviridae family. Most young children infected with EV71 develop mild symptoms of hand, foot and mouth disease, but some develop severe symptoms with neurological involvement. Limb paralysis from EV71 infection is presumed to arise mainly from dysfunction of motor neurons in the spinal cord. However, EV71 also targets and damages skeletal muscle, which may also contribute to the debilitating symptoms. In this study, we have delineated the impacts of EV71 infection on skeletal muscle using a mouse model. Mouse pups infected with EV71 developed limb paralysis, starting at day 3 post-infection and peaking at day 5-7 post-infection. At later times, mice recovered gradually but not completely. Notably, severe disease was associated with high levels of myositis accompanied by muscle calcification and persistent motor end plate abnormalities. Interestingly, macrophages exhibited a dynamic change in phenotype, with inflammatory macrophages (CD45+CD11b+Ly6Chi) appearing in the early stage of infection and anti-inflammatory/restorative macrophages (CD45+CD11b+Ly6Clow/-) appearing in the late stage. The presence of inflammatory macrophages was associated with severe inflammation, while the restorative macrophages were associated with recovery. Altogether, we have demonstrated that EV71 infection causes myositis, muscle calcification and structural defects in motor end plates. Subsequent muscle regeneration is associated with a dynamic change in macrophage phenotype.